Historisk geografi og regionaliseringer: Muligheder og problemstillinger - Dam, Peder (Hikuin, 2008)
Historical geography and regionalisations. Prospects and problems By Peter Dam Historical geography is an interdisciplinary discipline which attempts to combine the methodology of the two mother-disciplines history and geography as well as having its own methods. In this article the most commonly used historical sources, mapping techniques and historical-geographical methods seen in relation to regionalisation are discussed. The most commonly used historical-geographical sources are categorised into three main-groups: 1) relics, 2) present-day collection and classification of sources and 3) sources from the early modern period that can be used as guidelines for the landscape in early periods. Mapping techniques or type are categorised into area, line and point-based maps – plus rastermaps which belong to a separate category. Finally, four methods are described: retrogressive analyses, retrospective analyses, synchronic analyses and the regional comparative analyses. Historical regions produced by historical-geographical methods have boundaries following natural-geographical boundaries, mainly soil- and terrain variation, and administrative districts from the Middle Ages, mainly herreder (~ shires), sysler (local Jutish districts) and the three countries (Skåne, Sjælland and Jutland). Just to mention a few. The are no ‘main’ regional boundaries – there are many and various types of boundaries in the historical regions, depending on period, sources, methods and objective.